2020
DOI: 10.31332/lifalah.v5i1.1923
|View full text |Cite
|
Sign up to set email alerts
|

Kepemimpinan Islami dan Etika Kerja Islami: Pengaruhnya terhadap Kinerja Karyawan

Abstract: Kesuksesan sebuah perusahaan atau organisasi ditentukan oleh kemampuan pemimpin dalam membimbing dan menginspirasi bawahan untuk bersedia berkontribusi terhadap tujuan organisasi. Tidak hanya itu, etika kerja juga menjadi pendorong kinerja organisasi. Dari banyak studi yang membahas kepemimpinan dan etika kerja, masih terdapat banyak celah jika dikaitkan dengan perbedaan konteks penelitian dan perbedaan agama. Tujuan penelitian ini adalah untuk berkontribusi pada pengembangan konsep kepemimpinan islami dengan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 1 publication
2
9
0
1
Order By: Relevance
“…The above statement is supported by several previous studies which reveal factors that affect job performance, namely [5] and [4] which state that job insecurity has a negative and significant relationship to job performance, [8] and [9]. shows that Islamic work ethic has a positive and significant effect on performance, [10] and [11] state that employee engagement has a positive and significant effect on employee performance.…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…The above statement is supported by several previous studies which reveal factors that affect job performance, namely [5] and [4] which state that job insecurity has a negative and significant relationship to job performance, [8] and [9]. shows that Islamic work ethic has a positive and significant effect on performance, [10] and [11] state that employee engagement has a positive and significant effect on employee performance.…”
Section: Introductionsupporting
confidence: 71%
“…If you are able to achieve the performance target on time, it can be said that your performance is high. Previous research by [8] found that Islamic work ethic has a positive and significant influence on employee performance, so the third hypothesis is:…”
Section: E Hypotheses Developmentmentioning
confidence: 94%
See 3 more Smart Citations